Acclimatization of Eurycoma longifolia (Tongkat Ali) Plantlets to Ex Vitro conditions - Yahya, Muhammad Fuad; Hassan, Nor Hasnida; Abdullah, Nazirah; Abd. Rahman, Siti Suhaila; Ismai, Haliza; Abdullah, Mohd Zaki; Mohd Ariff, Farah Fazwa; Ngah, Mohamad Lokmal; Koter, Rosdi; Khalid, Rozidah; Abdullah, Rohani; Zakaria, Norfarhana; et al. (Universiti Malaysia Kelantan, 2015)
Eurycoma longifolia is one of the famous herbal plants with great medicinal benefits. The plant which also known as Tongkat Ali is well-known for treating erectile dysfunction and as energy booster. Tongkat Ali plantlets were produced using in vitro propagation technique to cater the demand for planting material. The development of successful acclimatization technique is prerequisite for in vitro propagation method. Acclimatization is a step to prepare the plantlets to survive and grow in different environment compare to laboratory. In this study, an attempt was made to identify the best potting media to acclimatize Tongkat Ali using glass chamber. Rooted plantlets about 2-4 cm height were used and subsequently transferred to different potting media for acclimatization i.e jiffy 7, sand, baked soil, mixture of cocoa peat and sand, sand and top soil and lastly cocoa peat and baked soil. Plantlets grown in jiffy 7 showed 100% survival followed by the mixture of cocoa peat and baked soil with 94.45% of survival. The acclimatized plantlets were transplanted into polybag and maintained in the shadehouse condition.